Westonci.ca is your trusted source for finding answers to all your questions. Ask, explore, and learn with our expert community. Experience the convenience of finding accurate answers to your questions from knowledgeable professionals on our platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.

we have first we replace the functions;sin x/1-cos x= cos x+cot xsin x/1-cosx=1/secx +cosx/sen xsin x/ 1-cos x =1/(1/cos x) + cos x/sen xsin x /sin x= 1/cos x + cos x/sen xsin x/sin x= (1/cos x=sin x) + cos x/sin x;sin x/sin x= sin(2) mean squared; +cos x;then the function remains sine squared x + cosine squared of xsin(2)x +cos (2) x = 1

Sagot :

we have first we replace the functions;



sin x/1-cos x= cos x+cot x

sin x/1-cosx=1/secx +cosx/sen x

sin x/ 1-cos x =1/(1/cos x) + cos x/sen x

sin x /sin x= 1/cos x + cos x/sen x

sin x/sin x= (1/cos x=sin x) + cos x/sin x;



sin x/sin x= sin(2) mean squared; +cos x;





then the function remains sine squared x + cosine squared of x

sin(2)x +cos (2) x = 1